Nurse’s Responsibility and Liability in Chemotherapy Formulation: Legal and Ethical Considerations - Rupinder Kaur (International Journal of Oncological Nursing and Practices, 2025)
Each year, over 16 million new cancer cases are diagnosed globally. Cancer causes cells to grow uncontrollably, potentially leading to the formation of tumors, immune system damage, and other debilitating effects that can be fatal. Common cancer treatments include surgery to remove tumors, chemotherapy, radiation therapy, hormonal therapy, and immunotherapy. Among these, chemotherapy plays a significant role, accounting for nearly half of the overall treatment approach. Chemotherapy drugs can be administered through various methods, but they are often nonselective, affecting both cancerous and healthy cells in numerous organs and tissues. While chemotherapy can be lifesaving for patients, the preparation and administration of these drugs come with significant risks, including teratogenic, mutagenic, and carcinogenic effects for both patients and healthcare workers. Therefore, it is essential that only nurses with specialized training in chemotherapy preparation be entrusted with these responsibilities. Ensuring the safety of both patients and healthcare providers is a key priority throughout the entire chemotherapy treatment process. Additionally, healthcare workers must be well-versed in proper procedures for cleaning chemotherapy spills. Beyond the patient’s well-being, the occupational health risks to healthcare workers handling these potent drugs must also be fully addressed to minimize exposure and ensure a safe working environment.
Keywords: cancer treatment; chemotherapy; healthcare workers; occupational risks; patient safety